FISIBILITAS PEMBELAJARAN HIGH ORDER THINKING SKILL (HOTS) PADA MATERI DINAMIKA ATMOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN (STUDI DI SMAN 2 DAN SMAN 3 BUKITTINGGI) - SISCA MEGAHANDANI; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This article was written to find out the feasibility of HOTS learning in terms of planning, implementation, and assessment aspects on material of Atmospheric Dynamics and Its Impact in Life. This research uses descriptive quantitative method. The population of this research are all Grade X students in SMAN 2 Bukittinggi dan SMAN 3 Bukittinggi who study Geography. The sampling uses Random sampling technique with the results of Class X IPS 4 at SMAN 2 Bukittinggi and X IPS 2 at SMAN 3 Bukittinggi. The results of the research are reviewed from (1) the lesson planning aspect of the two schools which is included in the very good category where they gets percentage of 91.67% and 89.58%. (2) the learning implementation aspect, there are differences in the students’ Advanced Learning Activities where SMAN 2 Bukittinggi gets a percentage of 71% -75% with a deficient category, while SMAN 3 Bukittinggi gets 74% -83% with deficient and good categories. (3) the aspect of LKPD’s assessment, in SMAN 2 Bukittinggi has not been included in the HOTS category, while SMAN 3 Bukittinggi has been already included in the HOTS category.